Kemampuan Literasi Budaya dan Kewargaan Mahasiswa PGSD Universitas Muhamadiyah Sidoarjo, Indonesia - Kurniawan, Machful Indra (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2023)
Cultural and civic literacy is part of the national literacy movement launched by the Ministry of Education and Culture in Indonesia. This initiative seeks to equip all Indonesian citizens with the essential skills to navigate and respond to the increasing diversity of the 21st century. The Primary School Teacher Education (PGSD) study program at University Muhammadiyah Sidoarjo (UMSIDA) recognizes the importance of this goal. It provides material content for learning about cultural and civic issues. Based on this, it is essential to conduct research on the cultural literacy and citizenship abilities of PGSD students at Universitas Muhammadiyah Sidoarjo in the 21st century to know the cultural literacy and citizenship abilities of students and provide references to further learning activities in developing cultural literacy and citizenship in PGSD students. The research was conducted in the 2021/2022 academic year, which is between February 2022 and June 2022. This research employed a descriptive study using the survey method with a sample of 136 semester II students who have taken civics courses. Data collection techniques were in the form of questionnaires and data analysis techniques using percentage techniques. The study results showed that the percentage shows 68.4%, namely, out of 136 students, 93 students have a relatively high range of scores in digital literacy skills and citizenship.